Togo : Staff Report for 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Debt Sustainability Analysis update highlights Togo's continued moderate risk of debt distress. After full Heavily Indebted Poor Countries (HIPC) assistance, Multilateral Debt Relief Initiative, and beyond HIPC assistance, Togo's external and public debt indicators improved significantly in 2010/11 and remained stable under the previous Extended Credit Facility-supported program. In 2012, Togo contracted significant external debt. Although debt indicators are projected to remain below the policy-relevant indicative thresholds in the 20-year period under the baseline scenario, Togo remains vulnerable to certain shocks and could breach the policy-relevant thresholds for the present value (PV) of debt to GDP, PV of debt to exports, PV of debt to revenue, and debt-service-to-revenue ratios under some alternative scenarios in the outer years.